2019
DOI: 10.1128/iai.00670-18
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Mepacrine against Clostridium perfringens Enterotoxin in a Mouse Model of Enterotoxemia

Abstract: Clostridium perfringens enterotoxin (CPE) is a pore-forming toxin that causes the symptoms of common bacterial food poisoning and several non-foodborne human gastrointestinal diseases, including antibiotic-associated diarrhea and sporadic diarrhea. In some cases, CPE-mediated disease can be very severe or fatal due to the involvement of enterotoxemia. Therefore, the development of potential therapeutics against CPE action during enterotoxemia is warranted. Mepacrine, an acridine derivative drug with broad-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Some studies in broilers presented the same results in intestinal morphology ( 34 37 ). Other studies found that the C. perfringens enterotoxin (CPE), which is the main toxin produced by C. perfringens type A, displayed a dose-dependent effect and CPE can induce the intestinal injury ( 38 40 ). These studies focused on the toxaemic outcome of toxin absorption from the intestine into the circulation, and they did not adequately examine the specific changes that occur during C. perfringens infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in broilers presented the same results in intestinal morphology ( 34 37 ). Other studies found that the C. perfringens enterotoxin (CPE), which is the main toxin produced by C. perfringens type A, displayed a dose-dependent effect and CPE can induce the intestinal injury ( 38 40 ). These studies focused on the toxaemic outcome of toxin absorption from the intestine into the circulation, and they did not adequately examine the specific changes that occur during C. perfringens infection.…”
Section: Discussionmentioning
confidence: 99%
“…Enterotoxemia caused by the action of ITX presents similarities between intestinal lesions and lesions caused by toxins from other strains of C. perfringens, which makes it difficult to apply the protocol used for enterotoxemia caused by C. perfringens type D. In addition, there are cross-reactions between ITX and iota-like toxins that make it difficult to determine the specificity of ITX in lesions (Uzal, 2004;Navarro et al, 2019).…”
Section: Diagnostic Methods For Enteric Diseasesmentioning
confidence: 99%
“…C. perfringens strains can cause intestinal infections, including enteritis and enterotoxemia due to the action of toxins in the intestine of infected animals and/or other organs (Sayeed et al, 2008). Toxin action has resulted in skin, subcutaneous and muscle tissue diseases, gas gangrene or malignant edema, most of which are mediated by one or more toxins produced by C. perfringens (Uzal et al, 2010;Freedman et al, 2015;Brandi et al, 2016) (Songer, 1996;Songer and Miskimmins, 2004;Navarro et. al., 2019).…”
Section: Diagnostic Methods For Enteric Diseasesmentioning
confidence: 99%
See 2 more Smart Citations